Heritability and intrafamilial aggregation of arterial characteristics - Seidlerová, Jitka; Bochud, Murielle; Staessen, J. A; Cwynar, Marcin; Dolejsová, Milena; Kuznetsova, Tatiana; Nawrot, Tim; Olszanecka, Agnieszka; Stolarz, Katarzyna; Thijs, Lutgarde; Wojciechowska, Wiktoria; Struijker-Boudier, Harry A; et al. (Journal of hypertension, 2008)
BACKGROUND: We investigated the heritability and familial aggregation of various indexes of arterial stiffness and wave reflection and we partitioned the phenotypic correlation between these traits into shared genetic and environmental components. METHODS: Using a family-based population sample, we recruited 204 parents (mean age, 51.7 years) and 290 offspring (29.4 years) from the population in Cracow, Poland (62 families), Hechtel-Eksel, Belgium (36), and Pilsen, the Czech Republic (50). We measured peripheral pulse pressure (PPp) sphygmomanometrically at the brachial artery; central pulse pressure (PPc), the peripheral augmentation indexes (PAIxs) and central augmentation indexes (CAIxs) by applanation tonometry at the radial artery; and aortic pulse wave velocity (PWV) by tonometry or ultrasound. In multivariate-adjusted analyses, we used the ASSOC and PROC GENMOD procedures as implemented in SAGE and SAS, respectively. RESULTS: We found significant heritability for PAIx, CAIx, PPc and mean arterial pressure ranging from 0.37 to 0.41; P < or = 0.0001. The method of intrafamilial concordance confirmed these results; intrafamilial correlation coefficients were significant for all arterial indexes (r > or = 0.12; P < or = 0.02) with the exception of PPc (r = -0.007; P = 0.90) in parent-offspring pairs. The sib-sib correlations were also significant for CAIx (r = 0.22; P = 0.001). The genetic correlation between PWV and the other arterial indexes were significant (rhoG > or = 0.29; P < 0.0001). The corresponding environmental correlations were only significantly positive for PPp (rhoE = 0.10, P = 0.03). CONCLUSION: The observation of significant intrafamilial concordance and heritability of various indexes of arterial stiffness as well as the genetic correlations among arterial phenotypes strongly support the search for shared genetic determinants underlying these traits.
Keywords: Environment; dospělí; hypertenze; Female; Phenotype; rodina; Adult; Belgie; ženské pohlaví; arteria brachialis; arteria radialis; aorta; lidé; Belgium; krevní tlak; Humans; Arteries; Hypertension; Male; Pulsatile Flow; Aged; Czech Republic; Radial Artery; Family; Česká republika; životní prostředí; lidé středního věku; Aorta; senioři; mužské pohlaví; fenotyp; pulzatilní průtok; Poland; Blood Pressure; Middle Aged; arterie; Brachial Artery; Polsko